WALL COLOR INFLUENCE OF OF LIGHT INTENSITY IN SPACE - Rahmaniah, Rahmaniah (Teknosains: Media Informasi Sains dan Teknologi, 2015)
This research aimed to determine the effect on the intensity of the color of the walls in the room lighting. The method used is an experimental method using luxmeter measuring instrument that serves to measure the magnitude of the intensity of the lighting in the room. The research was done by determining a space in a house facing the east is the bedroom. The rooms were used size 3 × 3 m2; There are 1 piece window in the room; room door closed position during data collection; room made homogeneous color (one color). Lamp used was Phillips 8 watt, lamp position facing down. Colors used consists of white, yellow, pink, green and blue. color changes done alternately after the wall is cleaned first of the colors that have been used previously. The condition of the room at the time of data collection was made in four conditions that condition the lights on and the windows closed; the condition of the lights on and the windows open; the condition of the lights went out and the windows open, the condition of the lights went out and closed the window. Data were collected at 06: 00-22: 00 pm and the distance to the floor lamp was set at 2 m and 3 m. The results showed the largest to the smallest light intensity in a row consists of white (for a distance of 2 m light illumination intensity of 60 Lux, for a distance of 3 m by 53 Lux), the intensity of illumination on the yellow (56 Lux for a distance of 2 m and 54 Lux for a distance of 3 m), pink (for a distance of 2 m light illumination intensity of 42 Lux, for a distance of 3 m of 38 Lux), green (for a distance of 2 m light illumination intensity of 41 Lux, for a distance 3 m of 38 Lux), and blue (for a distance of 2 m light illumination intensity of 39.6 Lux, for a distance 3 m of 39 Lux). Greatest intensity obtained at the second condition that the light is on and the windows open.